Case study of a telemarketing with emphasis on the conditions of jobs (Research, Society and Development, 2022)
Ergonomics can be understood as human factors, a scientific field focused on understanding the relationship between people and elements/systems, being multidisciplinarity and interactions of people with organization, environment and technology. Enabling projects and interventions aimed at improving health, comfort, safety and better productivity in an integrated way. In view of the above this article aims to analyze the jobs of telemarketing attendants and propose improvements in working conditions and the implementation of the risk management program (PGR). In this way, the ergonomic analysis of the work was developed, and a check list was applied, based on Annex II of regulatory standard 17, and then made the analysis of the results obtained from the non-conformities found, and later, the proposals for improvement and adaptations of furniture and equipment of the workstations were developed, and it was suggested the implemented occupational risk prevention program and risk management program to provide more comfort,  well-being, health and safety for Workers.